1995
DOI: 10.1210/endo.136.11.7588263
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mRNA for somatostatin receptor (sstr) types 2 and 5 in individual rat pituitary cells. A double labeling in situ hybridization analysis.

Abstract: To characterize cell specific expression of sstr subtypes in the pituitary we have analyzed mRNA for sstr1-5 in rat pituitary somatotrophs by reverse transcriptase polymerase chain reaction and determined the pattern and level of expression of mRNA for sstr subtypes 2 and 5 in individual pituitary cell subpopulations by double label in situ hybridization. Purified somatotrophs expressed mRNA for all 5 sstrs. In situ hybridization analysis revealed sstr5 mRNA in 70% of somatotrophs, 57% of thyrotrophs, 38% of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 12 publications
1
43
0
Order By: Relevance
“…Rat pituitary cells, as well as the GH3 pituitary cell line, express all five sst mRNA (31,34). In situ hybridization combined with immunohistochemistry (35) and reverse transcription (RT)-PCR in purified somatotrophs (36) revealed that rat somatotrophs express mRNA for all five ssts. In situ hybridization analysis revealed a relatively high level of sst4 (35) and sst5 (35,36) mRNA expression in somatotrophs as well as an important although lower expression of sst2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat pituitary cells, as well as the GH3 pituitary cell line, express all five sst mRNA (31,34). In situ hybridization combined with immunohistochemistry (35) and reverse transcription (RT)-PCR in purified somatotrophs (36) revealed that rat somatotrophs express mRNA for all five ssts. In situ hybridization analysis revealed a relatively high level of sst4 (35) and sst5 (35,36) mRNA expression in somatotrophs as well as an important although lower expression of sst2.…”
Section: Introductionmentioning
confidence: 99%
“…In situ hybridization combined with immunohistochemistry (35) and reverse transcription (RT)-PCR in purified somatotrophs (36) revealed that rat somatotrophs express mRNA for all five ssts. In situ hybridization analysis revealed a relatively high level of sst4 (35) and sst5 (35,36) mRNA expression in somatotrophs as well as an important although lower expression of sst2. A heterogeneous expression of SRIH receptor subtypes has also been demonstrated in human pituitary tumours (37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, sst5 mRNA was found in 38% of normal corticotrophs, and sstr2 in only 3% [26], whereas Mezey and coworkers [27] demonstrated sst2 in a large population and sstr5 in a small population of corticotrophs. Somatostatin influences ACTH secretion in pituitary cells in culture through inhibition of CRF-stimulated adenyl cyclase activity, and by preventing stimuluselicited calcium influx [28] over sstr2 and sstr5 receptor subtypes but not over sstr1, sstr3 or sstr4 [29].…”
Section: Discussionmentioning
confidence: 91%
“…Yet in another study only 38% of corticotrophs expressed somatostatin receptor subtype 5 (sst5) and 3% expresses somatostatin receptor subtype 2 (sst2) (67). While in contrast Smith et al found a predominance of sst2 rather than sst5 (68).…”
Section: Somatostatin Analoguesmentioning
confidence: 87%